Granulomatous lymphocytic interstitial lung disease in common variable immune deficiency: an in-depth clinical, immunological, functional and radiological exploration with a focus on its management, challenged by chronic CMV infection - Moratti, Mattia; Schifino, Gioacchino; Baccelli, Francesco; Ferrari, Simona; Magrini, Elisabetta; Bassi, Mirna; Guerrieri, Aldo; Zompatori, Maurizio; Lanari, Marcello; Conti, Francesca (Frontiers in Immunology, 2025)
BackgroundCommon variable immune deficiency (CVID) is the most prevalent inborn error of immunity (IEI), marked by diverse clinical-immunological phenotypes and significant immune-dysregulation, including granulomatous lymphocytic interstitial lung disease (GLILD). GLILD is a severe manifestation of CVID, contributing to reduced life expectancy and a challenging diagnosis due to its insidious and non-specific clinical course. Current management strategies for GLILD rely on expert opinion due to a lack of randomized controlled trials (RCTs).ObjectivesThis study aims to provide a comprehensive immunophenotypical characterization of CVID patients with and without GLILD, investigate predictive biomarkers for GLILD development, and explore therapeutic strategies, particularly during concomitant SARS-CoV-2 and chronic cytomegalovirus (CMV) infections.SourcesPrimary data were collected from a cohort of 25 patients with CVID who underwent high-resolution computed tomography (HRCT), immunophenotyping, and serum immunoglobulin analysis at diagnosis and after immunoglobulin replacement therapy. Existing literature on CVID and GLILD biomarkers, immunological profiles, and therapeutic interventions informed comparative analyses.ContentPatients with GLILD exhibited distinct immunophenotypical features, including reduced regulatory T-cells, CD8+ naïve, central memory T-cells, and B-cell subsets (memory and switched memory), alongside increased CD21low B-cells and naïve B-cells, indicative of chronic inflammation-driven immune activation. IgA and IgG4 concentrations were significantly lower in patients with GLILD at diagnosis. Immunosuppressive therapy, predominantly mycophenolate mofetil (MMF), demonstrated favorable clinical and functional outcomes, though radiological progression persisted in some cases. CMV infection in patients with GLILD on immunosuppressants resulted in favorable outcomes, underscoring the importance of personalized treatment strategies.ImplicationsThis study highlights novel immunological markers and clinical-radiological patterns as potential predictors for GLILD, advocating for their integration into diagnostic and monitoring frameworks to reduce reliance on invasive histopathology. Future research should focus on validating biomarkers and conducting RCTs to establish evidence-based guidelines for GLILD management.